2021
DOI: 10.3390/su14010043
|View full text |Cite
|
Sign up to set email alerts
|

Pro-Environmental Employee Engagement: The Influence of Pro-Environmental Organizational, Job and Personal Resources

Abstract: As organizations continue to respond to the existential challenge that is climate change, the extent to which employees engage in environmental sustainability is critical to that response. This study introduces new measures of pro-environmental employee engagement, pro-environmental job resources and pro-environmental meaningful work. Based on engagement theory, a model is tested that shows how perceived corporate environmental responsibility, pro-environmental job resources (supervisor support, involvement, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(39 citation statements)
references
References 94 publications
(139 reference statements)
4
34
0
1
Order By: Relevance
“…Change engagement therefore provides a more theoretically grounded and motivational expression of previously researched positive change-related constructs, such as openness to change, readiness for change, and commitment to change (Bouckenooghe et al, 2009;Arnéguy et al, 2018;Tsaousis and Vakola, 2018). Although researchers have shown that change-related organizational and job resources are associated with change engagement (Albrecht et al, 2022a), no research has yet examined the influence of a theoretically coherent set of change-related psychological resources on change engagement.…”
Section: Change Engagementmentioning
confidence: 99%
See 2 more Smart Citations
“…Change engagement therefore provides a more theoretically grounded and motivational expression of previously researched positive change-related constructs, such as openness to change, readiness for change, and commitment to change (Bouckenooghe et al, 2009;Arnéguy et al, 2018;Tsaousis and Vakola, 2018). Although researchers have shown that change-related organizational and job resources are associated with change engagement (Albrecht et al, 2022a), no research has yet examined the influence of a theoretically coherent set of change-related psychological resources on change engagement.…”
Section: Change Engagementmentioning
confidence: 99%
“…Consistent with this proposition, research has demonstrated employee psychological safety to be positively associated with performance and innovation (Baer and Frese, 2003;Frazier et al, 2017). Although May et al (2004) showed that psychological safety was also positively associated with employee engagement, as yet, no research has been conducted on the construct of change-related psychological safety or its association with positive employee attitudes to change (Albrecht et al, 2022a). As modeled in Figure 1, the current research aims to address the gap by testing the proposed association between change related psychological safety and change engagement (H3).…”
Section: Change-related Psychological Safetymentioning
confidence: 99%
See 1 more Smart Citation
“…Policy and legislation have been described as effective top-down means to promote pro-environmental practices in different countries and cultures. Examples of this are the reduction of poisoning practices promoted by the awareness of environmental legislation in Kenya (Didarali et al, 2022 ), the pro-environmental engagement of Australian employees following the introduction of corporate pro-environmental policies (Albrecht et al, 2021 ), and the increased environmental concern of Chinese citizens living in cities with more sustainability policies in place (Liu et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…In general, most research on employees in sustainability topics have been conducted in companies, for example, employees' proenvironmental behaviors [19], [20], [21], the role of employee commitment for green performance [22], the employees' attitude and performance [23], and the role of EP in the sustainability [24]. There is increasing, yet limited, research on other types of organizations [25], such as the effect of corporate social responsibility on job satisfaction and organizational commitment [26], green employee engagement in higher education organizations [27], and analyzing employees' green behavior in the public and private sectors [28].…”
Section: Introductionmentioning
confidence: 99%